2019
DOI: 10.1101/655506
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low Abundance of Circulating Tumor DNA in Localized Prostate Cancer

Abstract: Calagua. Portions of this research utilized the computational resources of the NIH HPC Biowulf cluster. 3 IN MEMORIAMThis work is dedicated to the memory of Dr. Valery Bliskovsky, who made invaluable contributions to this project.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…Based on pass-filter SNVs and indels identified from exome sequencing, 50 targets were selected randomly from 871 total calls for additional amplicon-based sequencing, with the exception of the TP53 Y236X nonsense alteration, which was subsequently included for verification 33,34 . Prior to nomination for targeted sequencing, each selected genomic coordinate was inspected in IGV and mutation calls falling in MAPQ < 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on pass-filter SNVs and indels identified from exome sequencing, 50 targets were selected randomly from 871 total calls for additional amplicon-based sequencing, with the exception of the TP53 Y236X nonsense alteration, which was subsequently included for verification 33,34 . Prior to nomination for targeted sequencing, each selected genomic coordinate was inspected in IGV and mutation calls falling in MAPQ < 10 were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…edu/cgi-bin/hgPcr] to prevent production of unintended amplicons for each patient-specific batch of targets. The forward and reverse primer sequences identified above were appended with adaptor sequences 33 at the 5′ end, complementary to Illumina Nextera full-length primers (IDT). Dual-barcoded sequencing adaptors were modified 33 to contain longer regions of complementarity and were ordered with NGSO-4 purity from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The half-life of ctDNA is estimated to be up to 2 hours, and is dependent on factors including cell turnover, tumour size, excretion in bodily fluids and degradation rate by circulating nucleases [4]. Therefore, in non-metastatic cancer, concentration ranges of ctDNA, considered as fractions of total cell-free DNA, vary between tumour types, ranging from undetectable in prostate cancer [5] to 0.02-3.2% in non-small cell lung cancer (NSCLC) [6]. The historically poor sensitivity of ctDNA testing, has restricted its integration into routine clinical practice in non-metastatic disease [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the levels of ctDNA observed in the BPH patients are extremely low, as reported in certain recent studies. Therefore, Hennigan and coworkers applied ultra-low-pass whole-genome sequencing to profile the cell-free DNA isolated from 112 patients with localized prostate cancer and concluded that the allele-specific alterations in ctDNA were below the threshold level required for detection [147].…”
Section: Prostate Cancermentioning
confidence: 99%